Help-Seeking Attitudes and Academic Stress Among Undergraduate Students - Sutanti, Natri; Kurniawan, Luky (Universitas Mercu Buana Yogyakarta, 2025)
University students' mental health and academic performance are significantly impacted by academic stress. This study looked at the academic stress levels, counseling experiences, emotional support networks, and help-seeking attitudes among 102 Indonesian undergraduate students between the ages of 19 and 24. The majority of students (71.6%) chose to ask friends for help, followed by parents (29.4%) and self-help (21.6%), according to the findings. Approximately half (52%) had sought counseling services, mostly in high school or college. Although some students expressed displeasure, the majority of counseling experiences were viewed as beneficial (60.4%). Only 4.9% of students reported high levels of academic stress, compared to the majority (81.4%) who reported moderate levels. Students who attended counseling did not significantly differ from those who did not in terms of their academic stress. This can happen due to limited respondents. While older students were more likely to seek therapy, stress levels and age did not significantly correlate. The results underline the value of peer support and draw attention to obstacles like stigma and accessibility that prevent people from formally seeking help. To further promote student well-being and academic success in Indonesian higher education, the study suggests expanding peer support programs, raising mental health awareness, and improving culturally relevant counseling services.